The Digitalization of Qur’anic Exegesis on Instagram: A Netnographic Study of @quranreview and Student Reception - Febriani, Ina Salmah; Sastra, Salwa Zharifah (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2026)
This study examines the digitalization of Qur’anic exegesis on Instagram through the case of @quranreview, an Islamic educational platform that presents Qur’anic messages in visual, concise, and youth-oriented formats. It focuses on how @quranreview makes tafsir accessible to young Muslim audiences and how students with Islamic studies backgrounds receive, evaluate, and negotiate its content. Using a qualitative netnographic approach, the study applies Cyber Media Analysis, which examines four levels: media space, media document, media object, and experience. Data were collected through online observation of @quranreview posts during July–August 2025, documentation of visual and textual content, follower engagement, Google Form responses, and interviews with six students from the Islamic Education Program and the Qur’anic Studies and Exegesis Program at UIN Sultan Maulana Hasanuddin Banten. The findings show that @quranreview functions as a form of popular tafsir on Instagram by connecting Qur’anic verses with contemporary issues such as anxiety, work, family, financial hardship, teachers’ welfare, public unrest, and youth motivation. Its visual design, accessible language, and affective tone make Qur’anic messages more relatable for millennial and Gen Z audiences. However, the study also finds that accessibility does not automatically guarantee exegetical authority. Several respondents appreciated the account’s relevance and visual appeal, but criticized the lack of explicit references to tafsir, hadith, or scholarly explanations in some posts. This study argues that @quranreview reflects both the opportunities and challenges of Instagram-based tafsir: it expands access to Qur’anic learning for young Muslims, but it also requires stronger source transparency, interpretive literacy, and scholarly accountability.